Avaliação do ciclo de vida (ACV) da produção de bioetanol hidratado em pequena escala: abrangência agrícola e industrial - Brondani, Michel (2014)
The state of Rio Grande do Sul (RS) produces little of the ethanol consumed because of edaphoclimatic conditions that preclude the extensive agricultural production and the consequent construction and operation of large distilleries. However, small-scale distilleries may supply, in part, this ethanol for consumption through production with sugarcane. The Life Cycle Assessment (LCA) and Energy Efficiency Analysis were performed to evaluate small-scale ethanol production considering the individual step and the overall analysis. The main results of the LCA were given in terms of environmental impacts and damage according to Eco-Indicator 99 assessment method, and demonstrated that nitrogen- and phosphorus- rich fertilizers along with herbicide and limestone were responsible for major environmental damage during the agricultural step, while the use of equipments and electricity had major impacts in industrial step. The agricultural step showed high energy efficiency (9.98-19.03 - energy in/energy out ratio) while the industrial stage showed energy efficiency of 0.86-0.87 and 0.20-0.21 with and without bagasse energy credits, respectively. In the overall analysis, the industrial step showed higher impacts and damages. Small-scale ethanol production chain presented energy efficiency (2.59-2.92) with bagasse energy credits. Otherwise the process could be energetically inefficient (0.61-0.69). Construction of the small-scale distillery and acquisition/sizing of equipment based on the availability of raw material supply are actions to avoid energy losses and environmental damage. The LCA was also used to evaluate, environmentally, the production of two types of distillation columns (tray type and mixed type) for continuous production of hydrous ethanol to indicate the model less impact on the environment. The results showed that the production of mixed distillation column generates lower contributions of impact to the environment, therefore their choice for installation in small-scale is indicated in terms of mitigating environmental impacts.